Replacement of Beef Fat in Meatball with Oleogels (Black Cumin Seed Oil/Sunflower Oil) - PALAMUTOĞLU, R (Journal of the Hellenic Veterinary Medical Society, 2021)
Meat products contain fatty acids, especially saturated fatty acids, which cause adverse health effects. The effect of fats on meat products isnot only concerned with health, but also about the product’s sensorial or textural properties. The research aimed to develop a new, healthier meatball formula in which the fat is substituted by oleogel gelled by carnauba wax and made with sunflower oil and black seed oil mixture. The effect of substituting animal fat with oleogel on color values, cooking parameters, lipid oxidation, and the textural properties of meatballs were determined. The effect of oleogel type on the TBA values of 50 and 75% substituted samples was statistically significant (p < 0. 05), and TBA values of the samples with oleogel substituted were higher than others at the end of the storage. The effect of substitution rates on the texture profile of meatball samples was found to be statistically significant (p <0. 05). The oleogel (25%) added group scored significantly (p < 0. 05)higher than the control group in appearance, flavor, texture, juiciness, oiliness, and overall acceptability, and was not found difference between the treatment groups.